CAMPUR KODE BAHASA PENYIAR RADIO REPUBLIK INDONESIA PRO 1 PEKANBARU - Desrah '; Hasnah Faizah AR; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the broadcaster mixed code language used by radio broadcasters of the Republic of Indonesia Pro 1 Pekanbaru. Prnrlitian is about mixed language source code used by broadcasters, the type of code-mixing and the predominant language used radio broadcaster of the Republic of Indonesia Pro 1 Pekanbaru. This study uses a qualitative approach with a recording technique that aims to mendeskdripsikan how mixed source language code used by broadcasters, the type of code-mixing and the predominant language used radio broadcaster of the Republic of Indonesia Pro 1 Pekanbaru. Results of the study are (1) the language source code used mixed radio broadcaster of the Republic of Indonesia Pro 1 Pekanbaru including English, Minang, Javanese, Malay, Betawi, Balinese and Sundanese. (2) types of code-mixing language radio broadcaster of the Republic of Indonesia Pro 1 Pekanbaru is mixed into the code and code-mixing to the outside. (3) the dominant language used radio broadcaster of the Republic of Indonesia Pro 1 Pekanbaru.Keywords: code-mixing, broadcasters,Radio Republik Indonesia